2015
DOI: 10.5861/ijrsp.2015.1055
|View full text |Cite
|
Sign up to set email alerts
|

The effects of pay satisfaction and affective commitment on turnover intention

Abstract: One of the antecedents of turnover and turnover intention is job attitude. Among the job attitudes in the organizations, many researchers have focused on satisfaction and organizational commitment as the factors affecting turnover intention. Meta-analysis studies have noted that correlation between turnover intention and commitment is higher relative to its relationship with satisfaction which indicates the possibility of mediation relationship. One facet of satisfaction which is important in predicting turnov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 36 publications
5
15
0
1
Order By: Relevance
“…This finding is consistent with an earlier study conducted by Siu [41] , who also found a positive relationship between the physical well-being of employees and affective commitment. According to Zeidan [44] , employees with high affective commitment demonstrate emotional attachment/identification with, and involvement in the organization, and such employees are less likely to engage in withdrawal behaviors such as absenteeism, low performance, and turnover [45] , [46] .…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with an earlier study conducted by Siu [41] , who also found a positive relationship between the physical well-being of employees and affective commitment. According to Zeidan [44] , employees with high affective commitment demonstrate emotional attachment/identification with, and involvement in the organization, and such employees are less likely to engage in withdrawal behaviors such as absenteeism, low performance, and turnover [45] , [46] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous researchers have distinguished three mindsets of commitment: affective, continuance, and normative commitment (Meyer & Allen, 1991). Affective commitment represents the highest form of identification with the unit/team and its goals and has a strong negative relationship with turnover intention (A'yuninnisa & Saptoto, 2015;Meyer & Herscovitch, 2001;Wagner, 2007). For this reason, we focused on only the affective component of commitment.…”
Section: Individual-level Predictorsmentioning
confidence: 99%
“…Joarder et al [40] examined the connection between affective commitment and turnover intentions, and showed that affective commitment has negatively and significantly impacted turnover intentions. Consistent with previous studies, A'Yuninnisa and Saptoto [41] examined the link between pay satisfaction and turnover intentions through affective commitment. It was found that pay satisfaction had a direct and indirect effect via affective organizational commitment on turnover intention.…”
Section: Job Embeddedness Job Satisfaction Affective Commitment Andmentioning
confidence: 58%